Prevention of Na Corrosion and Dendrite Growth for Long-Life Flexible Na–Air Batteries - Liu, Xizheng; Lei, Xiaofeng; Wang, Yong-Gang; Ding, Yi (ACS central science, 2021)
Rechargeable Na–air batteries (NABs) based on abundant Na resources are generating great interest due to their high energy density and low cost. However, Na anode corrosion in ambient air and the growth of abnormal dendrites lead to insufficient cycle performance and safety hazards. Effectively protecting the Na anode from corrosion and inducing the uniform Na plating and stripping are therefore of vital importance for practical application. We herein report a NAB with in situ formed gel electrolyte and Na anode with trace residual Li. The gel electrolyte is obtained within cells through cross-linking Li ethylenediamine at the anode surface with tetraethylene glycol dimethyl ether (G4) from the liquid electrolyte. The gel can effectively prevent H2O and O2 crossover, thus delaying Na anode corrosion and electrolyte decomposition. Na dendrite growth was suppressed by the electrostatic shield effect of Li+ from the modified Li layer. Benefiting from these improvements, the NAB achieves a robust cycle performance over 2000 h in opened ambient air, which is superior to previous results. Gelation of the electrolyte prevents liquid leakage during battery bending, facilitating greater cell flexibility, which could lead to the development of NABs suitable for wearable electronic devices in ambient air.